English file - Latham-Koenig, Christina. (Oxford University Press, 2012)
The English File third edition digital components help to make the most of teaching and learning opportunities inside and outside the classroom. The digital package includes: iTools (a digital classroom resource), iTutor and iChecker for students, Pronunciation App for mobiles, Online wrkbook,Student's and Teacher's websites.